PENANAMAN MANGROVE DI PANTAI MEKO DESA PLEDO SEBAGAI UPAYA PENCEGAHAN ABRASI: Planting Mangroves On Meko Beach In Pledo Village As An Effort To Prevent Abrasion - Yosep Arimatea Puan Keban; Mikael Thomas Susu; Yohana Fransiska Medho (Pakis Journal Institute, 2023)
Climate change, which is increasingly erratic, is a natural phenomenon that needs to be addressed. It is this kind of fact that should invite all parties to how to respond to such natural phenomena, especially the government as an agent of service and development. In line with such climate change, innovation in ecosystems in various aspects of human life has to be increasingly eroded and one of them is the threat to the sea. One of the alternatives for preserving marine ecosystems is innovation in sea reforestation. Mangrove which is a marine plant as a retention barrier for the potential for sand to erode and prevent abrasion is one of the superior alternatives. Mangrove forest ecosystem is an important habitat for biodiversity and as a coast guard from abrasion. This activity aims to increase public awareness about the importance of mangroves in preventing abrasion, especially in Meko Hamlet. This activity involved all village officials, youth youth organizations and residents of Meko Hamlet and MBKM students. In general, this activity went smoothly and was attended with quite high enthusiasm. It is hoped that with this activity, the community can understand and take advantage of the great benefits possessed by mangroves and prevent villages from abrasion. Mangrove planting as a prevention effort is an option that can be offered to Meko beach conservation, Pledo Village, Witihama District – East Adonara.